5. Analysis of thigh Death Chicken by Shear Values and Impedance Approach - Razali Razali; Denny Widaya Lukman (The Faculty of Veterinary Medicine of Syiah Kuala University, 2016)
Experiments were conducted to determine whether thigh meat from death chicken can be identified through Warner-Bratzler (WB) shear value and using the impedance value. Thirty of thigh meat (Biceps femoris) were obtained from commercial slaughtering house classified into three groups namely halal slaughtered healthy chicken (AHS), slaughtered death chicken (AMS), and slaughtered stressed chicken (ALS). Biceps femoris muscles were used to microscopic procedures and to assess WB score values and impedance values. This study showed that shear values of AMS thigh meat were lower than AHS and ALS after 5 and 9 h PM. This study indicated that the impedance value of AMS were significantly lower (P0.05) than AHS and ALS, it can be used to distinguish between halal thigh and the thigh meat from slaughtered death chicken.